(untitled) (Plant Bulletin, 2025)
Calendula (Calendula officinalis) cultivation often faces challenges related to seed germination and early plant growth, which can be influenced by the choice of growing media. This study aims to identify sustainable methods to improve Calendula’s seed germination, growth, and flowering performance using different growing media. The experiment was laid out in a completely randomized design (CRD) with three replications and six treatments: T0 (Soil - Top Soil, Garden Soil), T1 (Compost manure + Bagasse + Soil), T2 (Coconut husk + Thermacoal + Soil), T3 (Compost manure + Thermacoal + Soil), T4 (Coconut husk + Bagasse + Soil), and T5 (Vermicompost + Perlite + Soil). Parameters studied included seed germination (%), germination index, number of leaves per plant, days to flower initiation, flower diameter, flower fresh weight, flower dry weight, number of flowers per plant, plant height, and root length. Germination ranged from 28% to 97%, with soil-based and coconut husk + bagasse media showing superior performance. Vermicompost + perlite enhanced flowering traits, flower biomass, and plant height, while coconut husk + bagasse resulted in the poorest floral development. Root growth remained unaffected across treatments. Overall, vermicompost + perlite proved to be the most effective medium for promoting seed germination, vegetative growth, and flowering, emphasizing the importance of appropriate substrate selection for sustainable Calendula cultivation.